(30x+45)=(60x-45)

Simple and best practice solution for (30x+45)=(60x-45) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (30x+45)=(60x-45) equation:


Simplifying
(30x + 45) = (60x + -45)

Reorder the terms:
(45 + 30x) = (60x + -45)

Remove parenthesis around (45 + 30x)
45 + 30x = (60x + -45)

Reorder the terms:
45 + 30x = (-45 + 60x)

Remove parenthesis around (-45 + 60x)
45 + 30x = -45 + 60x

Solving
45 + 30x = -45 + 60x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-60x' to each side of the equation.
45 + 30x + -60x = -45 + 60x + -60x

Combine like terms: 30x + -60x = -30x
45 + -30x = -45 + 60x + -60x

Combine like terms: 60x + -60x = 0
45 + -30x = -45 + 0
45 + -30x = -45

Add '-45' to each side of the equation.
45 + -45 + -30x = -45 + -45

Combine like terms: 45 + -45 = 0
0 + -30x = -45 + -45
-30x = -45 + -45

Combine like terms: -45 + -45 = -90
-30x = -90

Divide each side by '-30'.
x = 3

Simplifying
x = 3

See similar equations:

| 6y=+11 | | 5=3a-3a+2 | | 9x-12=6x-15 | | -5g-4=1 | | 17x-5a-3x-4a= | | 4x+12=-9x-20 | | 55.53+x=95.44 | | -16-3k=6k-5k | | 9x-12=ax-b | | 90x^2-46x+180=0 | | 100-f=60 | | x-18=2/3 | | 4x+12=4x-20 | | 2c-5=-c+5 | | axoverc-b=coverb | | (21x^2-147x+210)=0 | | (8-5i)-(-3-7i)=0 | | 6-2n=6-2n | | 90+x=7x | | 14r-17=39 | | [t+5]+3=-12 | | w-200=100 | | 2y+14=24 | | 4(x+5)=4(x+14) | | .03x+.04(2000+x)=920 | | 15-3r=-6 | | -10x^3-45x^2+45x-30=0 | | 8-4x=2x-9 | | 7cos(2x)=6 | | -x+3=4x-17 | | 8x-7y=32 | | 4x+19y= |

Equations solver categories